Pengaruh Good Corporate Governance dan Kualitas Laba terhadap Nilai Perusahaan Manufaktur Sector Basic Material yang terdaftar di BEI tahun 2022-2024 - natasya, devi; Arisman, Anton (Universitas Multi Data Palembang, 2026)
This study aimed to determine whether good corporate governance and quality of income variables influence the value of manufacturing companies in the basic materials sector. This study used secondary data obtained from the Indonesia Stock Exchange (IDX), and employed a quantitative approach. A sample of 62 items was used in the testing. The results showed that good corporate governance had no effect on company value, and quality of income has a positive effect on company value.